THE AUSTRIAN SCHOOL AND VALUE INVESTING: AN APROXIMATION (II) - Yusta, Pablo (REVISTA PROCESOS DE MERCADO, 2022)
Abstract: There is no need to know the Austrian School to practice Value Investing nor to know what Value Investing means to understand the Austrian School; but it is interesting to detect the cross advantages that appear when approaching both fields of study. This second article of the trilogy will be divided into nine parts: the first one will serve as an introduction and the other eight will be used to develop different theories of the Austrian School that help us in our work as value investors. Keywords: Austrian School; Value Investing. JEL classification: B13; B25; B53; E14; G11; G32.